2018
DOI: 10.1038/emm.2017.270
|View full text |Cite
|
Sign up to set email alerts
|

PI3Kδ contributes to ER stress-associated asthma through ER-redox disturbances: the involvement of the RIDD–RIG-I–NF-κB axis

Abstract: Hyperactivation of phosphoinositol 3-kinase (PI3K) has been suggested to be a potential mechanism for endoplasmic reticulum (ER) stress-enhanced airway hyperresponsiveness, and PI3K inhibitors have been examined as asthma therapeutics. However, the regulatory mechanism linking PI3K to ER stress and related pathological signals in asthma have not been defined. To elucidate these pathogenic pathways, we investigated the influence of a selective PI3Kδ inhibitor, IC87114, on airway inflammation in an ovalbumin/lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…In our study, the selective PI3Kδ inhibitor IC87114 attenuated poly I:C-induced inflammatory responses in vivo and in vitro. Other investigators also have showed that IC87114 decreased neutrophilic inflammation in BALF to almost control level (51)(52)(53). These anti-inflammatory effects of IC87114 might contribute to prevention of asthma and COPD exacerbation.…”
Section: Discussionmentioning
confidence: 84%
“…In our study, the selective PI3Kδ inhibitor IC87114 attenuated poly I:C-induced inflammatory responses in vivo and in vitro. Other investigators also have showed that IC87114 decreased neutrophilic inflammation in BALF to almost control level (51)(52)(53). These anti-inflammatory effects of IC87114 might contribute to prevention of asthma and COPD exacerbation.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have suggested that PI3K‐δ and ER stress are involved in airway inflammation and remodelling (Kim et al, ). To confirm the pathological role of PI3K‐δ and ER stress, we examined the effects of the PI3K‐δ inhibitor IC87114 and the chemical chaperone 4‐PBA that regulates ER stress in an A. fumigatus ‐induced mouse model of airway inflammation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that PI3K-δ and ER stress are involved in airway inflammation and remodelling (Kim et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…DExD/H-Box Helicase 58 (DDX58), also known as reticonic acid induced gene I (RIG-I), activates and regulates the expression of various in ammatory factors, thereby initiating innate and speci c immune responses 20 . Many studies have shown that RIG-I plays an important role in the in ammatory response of asthma induced by viruses [21][22][23] . Human leukocyte antigen (HLA) is a gene complex closely related to human immune function.…”
Section: Discussionmentioning
confidence: 99%